Reversal of Hypolipidemia in Chronic Hepatitis C Patients After Successful Antiviral Therapy - Yuan-Hung Kuo; Tang-Wei Chuang; Chao-Hung Hung; Chien-Hung Chen; Jing-Houng Wang; Tsung-Hui Hu; Sheng-Nan Lu; Chuan-Mo Lee (Journal of the Formosan Medical Association, 2011)
Chronic infection with the hepatitis C virus (HCV) is associated with impaired lipid metabolism. The aim of this study was to determine the impact of antiviral response on the serial change of serum lipids in chronic HCV patients. Methods: A total of 165 consecutive patients with HCV infection were prospectively enrolled. Serum total cholesterol (TC) and triglyceride (TG) levels in these subjects were compared with age, sex and body mass index-matched healthy individuals and 55 patients with chronic infection with hepatitis B virus (HBV). Serum lipid levels were measured in 143 patients with chronic HCV infection receiving pegylated interferon plus ribavirin therapy at baseline, at the end of treatment, and at week 24 after the end of treatment. Results: Patients with chronic HCV infection had significantly lower total TC and TG levels than normal controls (both p < 0.001). Serum TC levels were lower in HCV patients than in those infected with HBV (p < 0.001). Pretreatment serum lipid levels were not independent factors associated with sustained virological response (SVR). Among patients achieving a SVR, serum TC and TG levels significantly increased from 165 ± 30 mg/dL and 100 ± 47 mg/dL at baseline to 191 ± 36mg/dL (p < 0.001) and 116 ± 77 mg/dL (p = 0.029) at week 24 posttreatment, whereas no evident change in lipid profile occurred in the non-SVR group. Conclusion: Our data suggest that chronic HCV infection is associated with hypocholesterolemia and hypotriglyceridemia, which can be reversed by successful eradication of HCV. The clinical significance of hypolipidemia reversal among SVR patients, such as the risk of coronary artery or cerebral vascular disease, should be further investigated.